The Influence of Social Media on The Development of Songket Entrepreneurship in Bukittinggi City - Emi Vovo Sembiring; Muhammad Giatman; Yuliana (Enrichment : Journal of Management, 2022)
The development of increasingly sophisticated technology requires business people to improve their product sales strategies. Businesses conducted in the conventional way will be difficult to compete in the era of globalization. One of the challenges faced moment is that numerous business people use advances in communication technology, similar as the use of social media, this will clearly be more profitable because it provides easy access to product deals, reaching numerous consumers. The author is interested in conducting exploration to find out how important influence the use of information communication technology similar as social media has on the development of songket entrepreneurship in the megacity of Bukittinggi. This study used descriptive qualitative method. Descriptive research is used to obtain data systematically about understanding. Qualitative research is research that aims to obtain information rationally. The results in this study can be seen from several aspects including social media being able to increase product sales results, always adapting to the times, product quality that must be maintained. From the analysis of the data obtained using interviews and literature studies, it can be concluded that sales by utilizing social media as a place of promotion can increase sales results, but cannot be separated from that of course the product is packaged as well as possible to attract buyers. The use of social media has an impact on the development of songket entrepreneurship in Bukittinggi.